Girls are 'driven to pubs', 1944 (1944)
1944 1939-1945 "Girls are 'driven to pubs', 1944" [T0172.jpg], 1944, Daily Mail This press cutting from the 'Daily Mail' of 25 October 1944 reports the concern of the TUC Women's Advisory Committee that the lack of social clubs for young women war workers resulted in their frequenting public houses.